Preliminary study on utilization of piliostigma thonningii (kargo) pods as feed resource for small ruminants in Wudil Local Government Area of Kano State, Nigeria. - Iliyasu, K. A.; Ashiru, R. M.; Ibrahim, U.; Sani, T.; Sariyyu, S.; Ado, F. H. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
A survey was conducted to examine the utilization of Piliostigma thonningii (Kargo) pods as feed resource for ruminants in Wudil Local Government of Kano State, Nigeria. A total of 100 structured questionnaires were administered to one hundred randomly selected livestock rearers in five wards of the Local Government during the months of November to May (dry season) of 2019. The results obtained showed that the respondents varied in age group from 15 to 65 years with majority within the 36 - 40 years (40.00%) group. Male and female respondents constituted 41 and 59%, respectively. All respondents (100) had some form of education and their familiarity with small ruminant rearing varied from 1 to 35 years. Most of the respondents (65%) had flock size of 21 - 40. Ruminant animals reared by the respondents varied from sheep (24.00%) to goats (45.00%), while those that kept both sheep and goat together were 26.50%. All the respondents (100%) had awareness of feeding Kargo pods as supplement during dry season and 50% of respondents had rearing experience of 1-15 years. However, most of the respondents formulated feeds by mixing sorghum chaff, cowpea husk, wheat bran and maize bran. The study concluded that farmers in Wudil Local Government Area had awareness on the potential of Kargo pods as feed resource and it’s being utilized with other crop residues to feed animals especially during dry season.